2021
DOI: 10.3389/fcosc.2021.748104
|View full text |Cite
|
Sign up to set email alerts
|

Mate Preference Plasticity in a Critically Endangered Frog: Implications for Conservation Breeding

Abstract: Variation in female mate preferences for male traits remains poorly understood (both among and within females), despite having important evolutionary and conservation implications, particularly for captive breeding. Here, we investigate female mate preferences for male advertisement call frequency, and determine whether preferences vary over repeated trials, in the critically endangered southern corroboree frog, Pseudophryne corroboree. We conducted a series of phonotaxis trials in a six-speaker arena where na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 91 publications
(146 reference statements)
1
2
0
Order By: Relevance
“…Males with low-frequency calls had higher mating and fertilization success than males with high-frequency calls (irrespective of call rate), a pattern that is relatively common in anurans (Wells 2007;Lesbarrères et al 2008). This outcome suggests that P. corroboree males with low-frequency calls are highly attractive and is in line with the results of our recent manipulative phonotaxis study, which found that P. corroboree females significantly preferred low-frequency male advertisement calls (Kelleher et al 2021b). Our findings strongly suggest that call frequency is an honest signal of male fertility and fertilization potential, as males with low call frequencies also had high fertilization success.…”
Section: Effect Of Calling Behaviorsupporting
confidence: 91%
See 2 more Smart Citations
“…Males with low-frequency calls had higher mating and fertilization success than males with high-frequency calls (irrespective of call rate), a pattern that is relatively common in anurans (Wells 2007;Lesbarrères et al 2008). This outcome suggests that P. corroboree males with low-frequency calls are highly attractive and is in line with the results of our recent manipulative phonotaxis study, which found that P. corroboree females significantly preferred low-frequency male advertisement calls (Kelleher et al 2021b). Our findings strongly suggest that call frequency is an honest signal of male fertility and fertilization potential, as males with low call frequencies also had high fertilization success.…”
Section: Effect Of Calling Behaviorsupporting
confidence: 91%
“…It is possible that female P. corroboree may weigh call rate more heavily when assessing males with higher call frequency or shorter calls, as opposed to when call frequency is low (which is likely highly attractive and an indicator of male quality) or when call duration is long (as this may act as a hyper stimulus). It is important to consider that patterns of female mate choice observed here could also reflect amongindividual variation in female preferences for particular traits (e.g., some females prefer high call frequency while others prefer low frequency) (Jennions et al 1995); however, our recent manipulative phonotaxis study in P. corroboree did not provide any evidence for among-individual variation in preferences for call frequency (Kelleher et al 2021b). Female mate choice decisions could also reflect variation in how females' weight multiple male attributes (e.g., females assess and combine information from multiple traits but some females weight call rate more heavily while others weight duration more heavily) (Castellano and Rosso 2007), or variation in investment strategies (e.g., level of investment in mate sampling) (Jennions and Petrie 1997;Rosenthal 2017).…”
Section: Effect Of Calling Behaviormentioning
confidence: 80%
See 1 more Smart Citation